THE ROLE OF LEADERSHIP STYLES IN ENCOURAGING AND IMPROVING TEAM PERFORMANCE IN ONE OF THE BIGGEST OIL & GAS GROUP OF COMPANIES IN ABU DHABI, UAE - Abudaqa, Anas; Faiz, Mohd; Dahalan, Norziani; Almujaini, Hasan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Abstract: The aim of the current study is to examine the impact of leadership styles such as transformational leadership, transactional leadership and participative leadership on the team performance of one of the biggest oil & gas group of companies in UAE. The goal also includes the moderating role of perceived organizational culture on the links of transformational leadership and team performance, transactional leadership team performance, participative leadership, and team performance. The employees who have at least one immediate boss and currently working in one of the biggest oil & gas group of companies are the respondent and data were gathered by using questionnaires and it was analyzed by using Smart-PLS. The results indicated that transformational leadership, transactional leadership, and participate leadership have positive nexus with team performance. The results also indicated that perceived organizational culture has positively moderates among the nexus of transformational leadership and team performance, transactional leadership team performance, participative leadership, and team performance. The regulators of this group of companies will be the foremost users who want to formulate policies regarding the leadership style that improves team performance.